Kaina kai palaia: sacred contemplations: in three parts - Gib, Adam (Thomas F. Torrance Collection., 1786)
1. A view of the covenant of works -- 2. A view of the covenant of grace -- 3. A view of the absolute and immediate dependence of all things of God.